Loss of molars in periodontally treated patients: a retrospective analysis five years or more after active periodontal treatment - Bettina Dannewitz (Blackwell Synergy, 2006)
Objectives: Evaluation of tooth loss in molars and prognostic factors for molar survival. Material and Methods: Five hundred and five molars in 71 patients (mean age 46 years; 40 females) were evaluated. The following inclusion criteria were required: periodontal therapy of at least one molar, at least 5 years of supportive periodontal therapy, and baseline assessment of furcation involvement (FI). Results: At baseline 200 of 505 molars exhibited no FI, 116 degree I, 122 degree II, and 67 degree III FI. Twenty-seven molars did not receive periodontal treatment; 127 molars were subjected to non-surgical therapy, and 227 to flap surgery. Tunnel preparation was performed on 14 molars, root resection on 20, regenerative therapy on 57 teeth, and 33 molars were extracted. During the average follow-up period of 107 months 38 molars were lost additionally. Molars with degree III FI had the highest mortality. A multi-level proportional hazard model revealed smoking, baseline bone loss, number of molars left, and degree III FI as risk factors influencing the retention time of molars. Conclusion: Overall periodontal therapy results in a good prognosis of molars. Degree III FI leads to a significant deterioration of prognosis. Beyond FI smoking, baseline bone loss, and number of molars left influence molar survival.